Aligning Supply Chain through Inventory Ownership Analysis and Performance of Manufacturing Firms in Kenya - Kimwaki, Benedict; Ngugi, Patrick; Odhiambo, Rommanus (International Journal of Supply Chain Management, 2022)
Purpose: The purpose of this study was to establish the influence of roe played by alignment of supply chain through inventory ownership analysis on the performance of manufacturing firms in Kenya. Methodology: Descriptive and cross-sectional research designs were adopted in this study. The population of the large sized registered members as per the directory is 461. This study employed Cochran's formula to sample 160 large manufacturing firms from the total population. A structured questionnaire was used to collect data, which was analysed both qualitatively and quantitatively. This study adopted a descriptive data analysis and inferential data analysis. The analyzed data was presented using tables, graphs and pie charts. Results: The findings of the study revealed that the relationship between inventory ownership analysis and performance was significant at 5% level of significance. The findings of the study revealed that majority of the firms had not effectively posited inventory ownership analysis through, embracing the analysis of acquisition related costs, maintenance related costs, majority had no analysis of salvage related costs. The p-value was 0.000 which indicated that the null hypothesis failed to be accepted at 5% level of significance hence inventory ownership analysis have a significant influence on performance of manufacturing firms in Kenya. The study concluded that through adoption of inventory ownership analysis, the operational costs were reduced as well as the reduction of lead time. Unique contribution to theory, practice and policy: While the existing transaction cost theory used in this study was validated, the study recommends that the policy makers and management of manufacturing firms should invest in acquisition related costs, maintenance related costs, salvage related costs since it influences performance positively. The policy makers hold a major role in determining how key sectors such as the manufacturing sector are run. The regulators and the legislators formulate policies and guidelines that guide on how manufacturing firms should carry out their operations including supply chain processes. The study also recommended that manufacturing firms policy makers should develop a policy and regulatory framework to accelerate effective implementation inventory ownership analysis to enhance their organizational performance.